Effects of Turmeric (Curcuma domestica) in Maintaining Reduced Raw Cattle Protein Levels - Unggul P Juswono; Johan A E Noor; Avika Dyah Respati (Natural B, Journal of Health and Environmental Sciences, 2013)
A biological tissue that exposed by gamma radiation is known to be ionized that cause heavily damage due to the presence of free radicals. One of the damage may occured in the protein molecules which cause decreaseing of protein level of the beef so it needs a research on the effect of turmeric yellow (as antioxidant) in the maintaining of the protein level of the beef. In this research, the sample were meats without added turmeric as a control and the other were meats added with turmeric and then irradiated using radioactive elements Cs-137 and Co-60. Protein levels were tested using the standart method to analyze the levels of soluble protein. The results showed that the addition of turmeric had an influence to keep the protein value of beef. This situation suggests that turmeric is an antioxidant that is very good in counteracting free radicals.